Tracked Changes. Fibre optic interconnecting devices and passive components. Basic test and measurement procedures. Examinations and measurements. Visual inspection of fibre optic connectors and fibre-stub transceivers Part 3-35, (28th February 2023) - British Standards Institution,
No abstract available